Society's View of Children with Special Needs Disabilities: Between Empathy and Stereotypes - Ramadhini, Shanaz; Sri Nurhayati Selian (Yayasan Insan Mulia Bima, 2025)
Children who experience abnormalities or disabilities in their physical condition, namely damage to the muscular, bone, and joint systems caused by disease, accidents, congenital, and brain damage are called children with disabilities. The purpose of collecting this data is to obtain the views of the community in the form of empathy and stereotypes directed at children with disabilities. This research method uses a qualitative research method. By using data collection techniques obtained from observation, interviews, and documentation, then analyzed to understand issues related to the community's views on children with special needs (physical disabilities). The subjects of this study focused on the surrounding community, namely, among others, the surrounding community and teachers at Special School. Based on the research that has been conducted, there are two results obtained regarding the community's views on children with special needs with disabilities. First, the community views that children with disabilities have problems in carrying out learning activities. In fact, children with disabilities do not have obstacles in carrying out learning activities. Second, the community has various stigmas towards children with disabilities, the stigma about children with disabilities in the form of empathy must be given correctly without looking down on children with disabilities. At first, the public's view of children with disabilities was a negative or stereotypical view, but this view slowly changed into a positive view along with the development of the times. Thus, it is hoped that the public's view of children with disabilities will be better, provide appropriate empathy and not be dominated by excessive stereotypes in society.